Further Results on Designs Arising from Some Certain Corona Graphs - Sumathi, M.P.; Alwardi, Anwar (Journal of Advances in Applied & Computational Mathematics, 2015)
In this paper, we determine the partially balanced incomplete block designs and association scheme which are formed by the minimum dominating sets of the graphs C3°K2, and C4°K2. Finally, we determine the number of minimum dominating sets of graph G = Cn°K2 and prove that the set of all minimum dominating sets of G = Cn°K2 forms a partially balanced incomplete block design with two association scheme.